The Penguin dictionary of modern history, 1789-1945 - Palmer, Alan, 1926- (Penguin reference books., 1983)
This dictionary looks at the personalities, events and ideas from 1789 to 1945. While the main emphasis is on British affairs and on political topics, this dictionary also records trends in the history of all the major regions of the world including the USA, Russia, Australia and Canada.